Hieracium todorovskii, a new species of Hieracium sect. Olympica (Asteraceae) from Baba Mt., North Macedonia - Teofilovski, Aco (Phytotaxa, 2026)
Hieracium todorovskii (Asteraceae) is described as a new species of H. sect. Olympica, endemic to Baba Mt. in southwestern North Macedonia. The species occurs sporadically within an area of ca. 30 km² at elevations between 1565 and 2205 m. Its morphology is intermediate between H. olympicum s.l. and H. sparsum, suggesting a possible hybrid origin. It is clearly distinguished from similar species of the genus by the following combination of characters: phylopodous habit; basal leaves entire to denticulate, acute; middle and upper parts of the stem with dark to blackish, patent simple hairs, 5.5–8.5(–10) mm long; involucres with ± numerous dark grayish to blackish simple hairs and dense stellate hairs; phyllaries up to 2.3 mm wide at the base, ± obtuse to subacute; achenes pale brown; and pappus grayish. Photographs of the holotype and living material are provided.